Water Reduction with Visible Light: Synergy between Optical Transitions and Electron Transfer in Au‐TiO2 Catalysts Visualized by In situ EPR Spectroscopy1. Issue 43 (12th September 2013) - Priebe, Jacqueline B.; Karnahl, Michael; Junge, Henrik; Beller, Matthias; Hollmann, Dirk; Brückner, Angelika
<x xml:space="preserve">Abstract</x> Golden electrons: Visible light excites conduction electron transfer from gold particles to support vacancies where they are taken up by protons to produce hydrogen. This transfer process was visualized by in situ EPR spectroscopy.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>